Thematic Progression of Higher Education Advertorials: A Case Study in English and Bahasa Indonesia - Sujatna, Eva Tuckyta Sari; Pamungkas, Kasno; Heriyanto, Heriyanto (Advances in Social Sciences Research Journal, 2018)
Many researchers do their research on advertorial but the one discussing thematic progression in advertorial is still limited. The word advertorial comes from two English words; they are advertisement and editorial as an English blending words. This research data focuses on higher education both in English and Bahasa Indonesia advertorials. This article tries to figure out the types of the thematic progression and the types of the theme in advertorial for higher education both in English and Bahasa Indonesia advertorials. The research method applied in this research is descriptive analysis. The data taken from advertorial both in English and Bahasa Indonesia are collected and they are analyzed based on the Halliday’s theory of thematic progression and the types of the each theme found in the data. The research discusses two main questions; firstly what type of thematic progression found in Bahasa Indonesia and English advertorials for higher education, and secondly what types of theme found in each theme in English and Bahasa Indonesia for higher education advertorial. After doing classification and analyzing the data, it is found that the thematic progression in English and Bahasa Indonesia advertorials has different pattern. The dominant thematic progression found in Bahasa Indonesia advertorial for higher education is zigzag theme pattern while the dominant one found in English advertorial for higher education is reiteration theme pattern. From the data found, both of Bahasa Indonesia or English advertorial, it is found that the dominant theme found in each clause of the data is ideational or topical theme.